Di Bawah Bayang Bayang “Otoritas” Tuhan (Studi Hermenutika Fikih Ala Khaled Abou Fadl) - Baedhowi Baedhowi (Institut Islam Nahdlatul Ulama Temanggung, 2017)
Islamic jurisprudence (fikih) in the daily life of Muslims becomes the vanguard of practical discourse of Islam. Unfortunately the epistemological islamic jurisprudence of fiqh scholarship from time to time becomes always narrowed. Such epistemological reduction or narrowmindedness epistemology in practical life often brings out dispositism, authoritarianism, and radicalism to the perpetrators. They claim their own truth while putting aside opinions differing from their excuse as the only truth of God. These truth claims are often monopolized as God’s authority. The attitude of authoritarianism and the epistemological reduction of fikih that author say as “the authority of God.” While the madzahib priests (Imam al-madzahib) and their successors are always open and tolerant in accepting and appreciating different opinions. In this paper Abou Fadl tries to re-criticize the temporality and partial discourse of fikih and tries to restore the epistemology of fukih to the syar’iah region globally. The reconstruction of the partiality and locality of legal-formal fiqh discourse toward the shari’a region becomes significant in the contemporary era. The return of fiqh discourse to the epistemology of shari’ah as a whole is a necessity for contemporary context to contruct the building of Islamic morality as a practical, tolerant and humanis praxis islamic discourse.